THE URGENCY OF RECOGNIZING AND PROTECTING THE RIGHTS OF CUSTOMARY LAW COMMUNITIES TO NATURAL RESOURCES IN MINING MANAGEMENT: A REVIEW OF THE PERSPECTIVE OF ISLAMIC LAW - Istanto, Yusuf; Surya, Faizal Adi; Wardhani, Lidya Christina; Setiyowati, Fariska Jihan (Al Maqashidi : Jurnal Hukum Islam Nusantara, 2025)
This paper aims to examine the regulation of recognition and protection of customary law communities in mining management, and to review its suitability from an Islamic legal perspective. The method used is normative legal research with a legislative approach, especially regarding mining law policies and the existence of customary law communities. The results of the study indicate that the mining sector is a national strategic sector, but in practice it often causes conflicts with customary law communities that depend on their customary land for their livelihoods. Although the constitution and several regional regulations have recognized the existence of customary communities, there are no comprehensive regulations in the mining sector. The lack of synchronization between regulations causes legal uncertainty and weak protection for customary communities. From an Islamic legal perspective, recognition of land and resource rights by customary communities is part of the principles of justice (‘adl), welfare (maṣlaḥah), and protection of property (ḥifẓ al-māl). Therefore, this paper recommends the ratification of the Customary Law Community Bill as an important step in realizing structural justice and protection of the rights of customary communities in an integral manner, including in the mining sector. The bill is expected to provide legal certainty, become a reference for other sectoral regulations, and ensure that natural resource management is carried out fairly and sustainably in accordance with Islamic values.